UNFORESEEN COMPLICATION OF TRAMADOL ADMINISTRATION: A CASE REPORT - CHANDRAKAR, YUGAL (Asian Journal of Pharmaceutical and Clinical Research, 2024)
We present a detailed case report of a 22-year-old male patient admitted with severe back pain who experienced an unexpected complication following tramadol administration. Despite initial investigations showing no abnormalities, the patient developed convulsions shortly after receiving tramadol. This case underscores the importance of considering rare adverse reactions when administering medications, even in patients without a predisposing medical history.